1991
DOI: 10.1177/026765839100700204
|View full text |Cite
|
Sign up to set email alerts
|

Speaking to many minds: on the relevance of different types of language information for the L2 learner

Abstract: This paper re-analyses the notion of consciousness raising in language learning. The process by which language input becomes salient to the learner is termed 'input enhancement'. This process can come about as a result of deliberate manipulation, or it can be the natural outcome of some internal learning strategy. It can vary quantitatively and qualitatively, not necessarily involving conscious analysis of rules. Externally induced salience may not necessarily be registered by the learner and even when it is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
201
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(223 citation statements)
references
References 11 publications
8
201
0
2
Order By: Relevance
“…In other words, some conscious attention is required when adults intend to learn the grammar of a language because they do not have access to the language learning ability they had as a child (Schmidt, 1983). Focus on Form instruction intends to raise learners' consciousness toward the target structure they are exposed to while learning a language (Sharwood Smith, 1981, 1991. Input flood and input enhancement are two of the activities that can raise learners' consciousness and facilitate learning grammar.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…In other words, some conscious attention is required when adults intend to learn the grammar of a language because they do not have access to the language learning ability they had as a child (Schmidt, 1983). Focus on Form instruction intends to raise learners' consciousness toward the target structure they are exposed to while learning a language (Sharwood Smith, 1981, 1991. Input flood and input enhancement are two of the activities that can raise learners' consciousness and facilitate learning grammar.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…To promote learning, the learner should pay attention to forms, functions and contextual features but due to the non-saliency and infrequency of some forms, there should be a focused attention to learning (Schmidt, 1993(Schmidt, , 1995(Schmidt, , 2001. In this regard, Sharwood Smith (1991Smith ( , 1993 suggests Input Enhancement (IE) techniques (e.g. stress in speech or boldfacing in printed text) by which language input becomes salient to the learner.…”
Section: A Input Enhancement and Ilpmentioning
confidence: 99%
“…To improve learner"s language learning they should be provided with a variety of consciousness-raising activities. Sharwood Smith (1991) has proposed that the term consciousness-raising can be replaced by "input enhancement " because he believed that the instructor can only know that some aspects of input are highlighted in some way, but it is impossible to tell whether the learner"s consciousness has been raised. Different studies reported a variety of findings about the relation between glossing, reading comprehension, and incidental vocabulary learning.…”
Section: Phrasal Verbsmentioning
confidence: 99%